Characterizing the dairy value chain from an agroecological perspective in the peri-urban area of Bobo-Dioulasso, Burkina Faso's 'Agroecological Living Landscape' focus area / Caractérisation de la filière lait au regard de l’agroécologie dans la zone périurbaine de Bobo-Dioulasso, aire d’intervention du « Living Landscape Agroécologie » au Burkina Faso - Sib, Ollo; Vall, Eric; Corniaux, Christian; Sodré, Etienne; Sanogo, Souleymane (2023)
The overall purpose of this background paper is to provide a review of current knowledge on the local dairy value chain in the Hauts-Bassins region (Bobo-Dioulasso) in relation to the principles of agroecology. The study involved a review of available literature, followed by interviews with managers of Bobo-Dioulasso's dairy platform, as well as managers of Dairy Processing Units (DPUs), Milk Collection Centres (MCCs) and farmers' cooperatives. Documents reviewed include journal articles, graduate theses and dissertations, and study reports on Burkina Faso's dairy value chain, with particular emphasis on the Bobo-Dioulasso region.